2009
DOI: 10.1292/jvms.71.535
|View full text |Cite
|
Sign up to set email alerts
|

Use of Formalin-Fixed Paraffin-Embedded Tissue and Single-Strand Conformation Polymorphism Analysis for Polymerase Chain Reaction of Antigen Receptor Rearrangements in Dogs

Abstract: ABSTRACT. PCR for antigen receptor gene rearrangement analysis (PARR) is a new diagnostic method for lymphoid neoplasia. In PARR using formalin-fixed paraffin-embedded tissues (PARR-FFPE), control DNA amplification was successful in only three of five samples. The formalin fixation times of the three samples were shorter than those of the others. Analysis of the formalin fixation time and DNA amplification controls suggested that a formalin fixation time of less than one week is appropriate. Additionally, appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…These samples were originated from years of 1997, 2006, 2011 and 2012. It has been reported that not long‐term paraffin‐embedding but the formalin fixation time for more than 1 week can impede PCR . Since the fixation time at our institute is limited to 24–48 hours, we attribute the negative results of PCR with Cmu primers to small tissue sample sizes, which may have increased formalin permeability into tissue samples and thus intensified negative effects by formalin fixation on PCR …”
Section: Discussionmentioning
confidence: 98%
“…These samples were originated from years of 1997, 2006, 2011 and 2012. It has been reported that not long‐term paraffin‐embedding but the formalin fixation time for more than 1 week can impede PCR . Since the fixation time at our institute is limited to 24–48 hours, we attribute the negative results of PCR with Cmu primers to small tissue sample sizes, which may have increased formalin permeability into tissue samples and thus intensified negative effects by formalin fixation on PCR …”
Section: Discussionmentioning
confidence: 98%
“…Removal of paraffin from the tissue is the most critical step for successful extraction as undissolved paraffin which leads to poor sample quality and inhibition of PCR amplification [12]. Naoki Kaneko et al, demonstrated that formalin fixation time and percentage play an important role in getting good quality of amplifiable DNA for PCR analysis [13]. There is another factor, quantification of DNA which also influence the PCR results from FFPE tissue DNA.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid diagnostic errors, it is necessary to determine the reliability of the results of PARR. Single-strand conformation polymorphism is useful for verifying the results of conventional PARR, 6 but the procedure involved is relatively complicated and time consuming. On the other hand, heteroduplex analysis is reportedly useful to distinguish clonal reactions from pseudoclonal ones in cats 9 and dogs 11 .…”
mentioning
confidence: 99%